2022
DOI: 10.1002/app.53039
|View full text |Cite
|
Sign up to set email alerts
|

Development of material extrusion 3D printing compatible tailorable thermoplastic elastomeric materials from acrylonitrile butadiene styrene and styrene‐(ethylene‐butylene)‐styrene block copolymer blends

Abstract: Currently, material extrusion‐based additive manufacturing (MEAM) is an advanced fabrication technique for polymeric materials. However, MEAM feedstocks typically rely on amorphous thermoplastics and hence it suffers from limitation of compatible polymers. The current work reports the manufacturing of MEAM compatible new thermoplastic elastomers (TPEs) from acrylonitrile butadiene styrene (ABS) and styrene‐(ethylene‐butylene)‐styrene (SEBS) block copolymer blends which allow the designing of tailorable TPEs. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…These techniques differ fundamentally in terms of feeding material, speed, and printing technology. On a commercial scale, FDM is a highly utilized additive manufacturing technique, however, the technique is challenging for printing soft polymeric material [9][10][11]. In the FDM process material in the form of a filament is fed with the aid of counter-rotating rollers into the heated liquefier head.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques differ fundamentally in terms of feeding material, speed, and printing technology. On a commercial scale, FDM is a highly utilized additive manufacturing technique, however, the technique is challenging for printing soft polymeric material [9][10][11]. In the FDM process material in the form of a filament is fed with the aid of counter-rotating rollers into the heated liquefier head.…”
Section: Introductionmentioning
confidence: 99%
“…While improved printability is required to achieve high precision and reliability in the manufacturing of intricate geometries. Some efforts have been made to overcome these issues with the aid of a suitable compatibilizer that minimizes the interfacial tension between immiscible polymer blends 19–22 . Jairui Hou, Ming Zhong et al, demonstrated good mechanical performance and 3D printability of the components aided by polypropylene grafted with maleic anhydride (PP‐g‐MA) as a compatibilizer in brominated butyl rubber/polypropylene/thermoplastic vulcanization blends (BIIR/PP/TPV) 23 using the FDM process.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic elastomer (TPE) is a soft polymeric material that typically consists of a hard thermoplastic segment that provides thermoplastic-like processability and a soft rubbery segment that provides rubber-like elasticity. 24,25 TPEs are used in a wide range of industrial applications due to their good processability, unique rubber-like elasticity, and excellent mechanical properties. 9,26 Among the different classes of block copolymers, styrene-isoprene-styrene (SIS) block copolymer is an interesting commercial TPE.…”
Section: Introductionmentioning
confidence: 99%